UPAYA MENINGKATKAN KETERAMPILAN MENULIS GEGURITAN BERDASARKAN CERKAK MELALUI PENERAPAN METODE MIND MAPPING (PETA PIKIRAN) - Puspita, Oktaviani Windra (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2015)
This research aims to improve the learning quality and short story-based geguritan (poetry Japanese language) writing skill of the IX A graders of SMP Negeri 26 Surakarta using mind mapping method. This study was taken place in the XI A grade. The research strategy used was a descriptive qualitative one; the subject of research was the students and teachers; the data source of research included short story-based geguritan writing learning process event, teacher and students, as well as relevant document. Techniques of collecting data used in this research were interview, observation, document analysis, test, and documentation. The data validation tests used in this research were method triangulation, source triangulation and informant review. Technique of analyzing data used was a critical-comparative analytical descriptive one. The result of research showed that the quality of short story-based geguritan writing learning of the IX A graders of SMP Negeri 26 Surakarta improved significantly. It could be seen from the mean value of student performance observation sheet of 59.30% in cycle I, 84.87% in cycle II, 90.60% in cycle III, and the mean value of teacher performance of 66.70 in cycle I, 82.14% in cycle II, and 88.90% in cycle III . The short story-based geguritan writing skill of the IX A graders of SMP Negeri 26 Surakarta also improved significantly. It was indicated by the geguritan writing, mean class, and classical passing the IX A graders had achieved. The mean score of geguritan writing skill test in cycle I was 68.00% with passing of 46.42%. In cycle II, it increased to 75.10% with passing degree of 71.42% and in cycle III it increased to 82.82% with passing degree of 85.71%.